The decay of 140 La - Karlsson. S. E.; Svanh, V.; Petterson, H.; Malmsten, G.; Yuthman de Aisenberg, E. (North Holland Publishing, 1967)
Fil: Karlsson. S. E. Institute of Physics, University of Uppsala; Suecia